A high performance sealant and its preparation method and application

By using modified flame retardants and reinforcing fillers in sealants, combined with specific polymers and cross-linking agents, the deficiencies in mechanical strength, adhesion and flame retardancy of existing sealants are solved, and high performance is achieved. Preparation of performance sealant with excellent temperature resistance and light aging resistance.

CN118530690BActive Publication Date: 2025-01-21CAS APPLIED CHEM MATERIALS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410674544.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-28
Publication Date
2025-01-21
Estimated Expiration
2044-05-28

AI Technical Summary

Technical Problem

The existing sealants still have shortcomings in terms of mechanical strength, adhesion and flame retardant fire resistance, especially in high-temperature and high-pressure environments and long-term sunlight exposure.

Method used

It uses α,ω-dihydroxypolydimethylsiloxane as the base polymer, combined with vinyl silicone oil and hydrogen-containing silicone oil, and is modified by using materials such as zirconium silicate microbeads, nano-aluminum silicate and nano-silica. It is a flame retardant, combined with fumed silica and silicon nitride as reinforcing fillers, coupled with coupling agents and cross-linking agents to form a high-performance sealant.

Benefits of technology

The flame retardant performance, mechanical properties, temperature aging resistance and light aging resistance of the sealant are significantly improved, allowing it to show excellent bonding effect and stability in high temperature and high pressure environments and long-term sunlight exposure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004863663330000101
    Figure BDA0004863663330000101
Patent Text Reader

Abstract

The invention discloses a high-performance sealant and a preparation method thereof. The sealant comprises the following components in parts by weight: 100 parts of alpha, omega-dihydroxy polydimethylsiloxane, 10-25 parts of vinyl silicone oil, 5-10 parts of hydrogen-containing silicone oil, 10-40 parts of a flame retardant, 5-10 parts of fumed silica, 3-8 parts of silicon nitride, 10-15 parts of a coupling agent, 10-20 parts of a cross-linking agent and 0.1-1 parts of a catalyst; the flame retardant is prepared by reacting zirconium silicate microbeads, nano-aluminum silicate, nano-silicon dioxide, sodium carboxymethyl cellulose and pentaerythritol dimethacrylate; the sealant obtained by the preparation method of the invention has excellent flame retardant performance, mechanical performance, heat aging resistance and light aging resistance, and has good application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sealants, and in particular to a high-performance sealant and a preparation method and application thereof. Background Art

[0002] Silicone sealant is usually a sealing material composed of base rubber, filler, cross-linking agent and other additives. It has strong bonding strength and is widely used in curtain wall doors and windows and home decoration. It can effectively improve the building's waterproof sealing, thermal insulation and other properties.

[0003] In recent years, fires in high-rise buildings have occurred frequently. The gaps between curtain walls and each floor slab and partition wall should be sealed with fire-resistant sealing materials. Buildings have higher and higher requirements for fire-resistant sealants, and the demand is increasing.

[0004] Existing sealants still have deficiencies in mechanical strength, adhesion and inherent flame retardancy.

[0005] Patent CN116694288B discloses a flame-retardant modified silane sealant and a preparation method thereof, comprising the following raw materials: 100 parts of terminal silane polyether, 60-100 parts of filler, 30-40 parts of plasticizer, 18-24 parts of auxiliary agent, 1-1.6 parts of catalyst, 5-9 parts of dehydrating agent, and 0.6-1 part of adhesion promoter; the patent not only promotes cross-linking of the matrix through the addition of auxiliary agents, but also enables the sealant to form a denser network structure and improve the temperature resistance and tensile strength of the sealant. However, the patent adds too high a content of filler, and the inorganic powder is easy to agglomerate, which will affect the mechanical properties, adhesion and stability of the sealant.

[0006] Patent CN109762514B discloses a method for preparing an environmentally friendly silicone sealant, which is characterized by using a complex of organic bismuth and ionic liquid as a catalyst. The catalyst replaces the traditional organic tin catalyst, improves the environmental performance of the sealant, and the addition of ionic liquid improves the dispersion effect of the catalyst in the reactor, further improves the catalytic efficiency and reaction activity. The flame retardant in the patent is a conventional inorganic powder material. The patent does not improve the flame retardant effect of the sealant, which remains at the conventional level.

[0007] Therefore, it is necessary to continue to develop sealants with better high temperature resistance and fireproof sealing properties, improve their performance in outdoor applications under long-term sunlight exposure and in high temperature and high pressure environments, and improve their fire retardant properties. Summary of the invention

[0008] The purpose of the present invention is to provide a high-performance sealant and a preparation method and application thereof, to provide a sealant with excellent flame retardant properties and mechanical properties, and also with excellent heat aging resistance and light aging resistance, to meet the use requirements in outdoor sunlight exposure and high temperature and high pressure environments.

[0009] To this end, the present invention adopts the following technical solutions:

[0010] The invention provides a high-performance sealant, comprising the following components in parts by weight: 100 parts of alpha, omega-dihydroxy polydimethylsiloxane, 10-25 parts of vinyl silicone oil, 5-10 parts of hydrogen-containing silicone oil, 10-40 parts of flame retardant, 5-10 parts of fumed white carbon black, 3-8 parts of silicon nitride, 10-15 parts of coupling agent, 10-20 parts of crosslinking agent and 0.1-1 part of catalyst; the preparation method of the flame retardant is as follows: 1) adding water to zirconium silicate microbeads, nano aluminum silicate and nano silicon dioxide to fully grind to obtain a mixture; 2) adding sodium carboxymethyl cellulose and pentaerythritol dimethacrylate to a solvent, stirring, adding the above mixture, controlling the reaction temperature to 40-50 DEG C, and drying to obtain the flame retardant.

[0011] As a preferred technical solution, the mass ratio of the zirconium silicate microbeads, nano-aluminum silicate, nano-silicon dioxide, sodium carboxymethyl cellulose and pentaerythritol dimethacrylate is 3-5:1-2:1-2:5-10:10-20.

[0012] As a preferred technical solution, the particle size of the zirconium silicate microbeads is 1-10 μm.

[0013] As a preferred technical solution, the particle size of the nano-aluminum silicate is 1-100nm;

[0014] More preferably, the particle size of the nano-aluminum silicate is 20-50 nm.

[0015] As a preferred technical solution, the particle size of the nano-silicon dioxide is 1-100nm;

[0016] More preferably, the particle size of the nano-silicon dioxide is 20-50 nm.

[0017] As a preferred technical solution, the stirring rate is 200-700 r / min, and the stirring time is 30-90 min.

[0018] As a preferred technical solution, the mass ratio of the flame retardant: fumed silica: silicon nitride is 3-5:1-2:0.3-2.

[0019] As a preferred technical solution, the coupling agent is one or more of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and γ-(2,3-epoxypropyl)propyltrimethoxysilane.

[0020] As a preferred technical solution, the crosslinking agent is one or more of methyltriacetoxysilane, ethyltriacetoxysilane, propyltriacetoxysilane, methyltributylidene oxime silane and di-tert-butoxydiacetoxysilane.

[0021] As a preferred technical solution, the catalyst is one or more of dibutyltin bis(acetylacetonate), dibutyltin diacetate, and dibutyltin dilaurate.

[0022] The present invention also provides a method for preparing a high-performance sealant, comprising the following steps:

[0023] 1) Disperse and stir α, ω-dihydroxy polydimethylsiloxane, vinyl silicone oil, hydrogen silicone oil and crosslinking agent for 20-30 minutes; 2) Add flame retardant, fumed silica and silicon nitride and stir at high speed for 25-40 minutes;

[0024] 3) Add coupling agent and catalyst, evacuate, disperse and stir evenly, and then discharge.

[0025] The present invention also provides an application of the high-performance sealant, which includes the bonding of door and window materials, the bonding of assembled building components, the bonding of fireproof facility materials and the bonding of automobile materials.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] The present invention uses α, ω-dihydroxy polydimethylsiloxane as a base polymer, and is combined with hydrogenated silicone oil with good waterproof effect and ethylene-based silicone oil with excellent high and low temperature performance, low surface tension and good fluidity, so as to enhance the mechanical properties, fluidity and stability of the base polymer.

[0028] The flame retardant of the present invention first uses zirconium silicate microbeads to load nano aluminum silicate and nano silicon dioxide, and then modifies them with sodium carboxymethyl cellulose and pentaerythritol dimethacrylate, which can greatly improve the dispersibility and adhesion of the composite material composed of zirconium silicate microbeads, nano aluminum silicate and nano silicon dioxide, and significantly improve the flame retardant performance and mechanical properties of the material.

[0029] The invention adopts fumed white carbon black and silicon nitride as reinforcing fillers, which can improve the flame retardant property and mechanical property of the sealant.

[0030] The applicant unexpectedly discovered that the flame retardant has a synergistic effect with fumed silica and silicon nitride, and their combined use significantly improves the flame retardant and mechanical properties of the sealant.

[0031] The sealant prepared by the invention has excellent flame retardancy, mechanical properties, heat aging resistance and light aging resistance, and has good application prospects. DETAILED DESCRIPTION

[0032] The specific implementation methods of the technical solution of this specification are further described below through specific examples. These examples are for the purpose of describing the technical solution in detail, rather than for limiting the technical solution. Based on the examples in this specification, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this specification.

[0033] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0034] Example 1

[0035] This embodiment provides a high-performance sealant, comprising the following components in parts by weight:

[0036] 100 parts of α,ω-dihydroxy polydimethylsiloxane, 20 parts of vinyl silicone oil, 5 parts of hydrogen silicone oil, 30 parts of flame retardant, 5 parts of fumed silica, 5 parts of silicon nitride, 10 parts of coupling agent, 15 parts of crosslinking agent, and 0.25 parts of catalyst;

[0037] The preparation method of the flame retardant is:

[0038] 1) Add 5 g zirconium silicate microbeads, 2 g nano aluminum silicate, and 2 g nano silicon dioxide into 10 mL water and grind thoroughly to obtain a mixture;

[0039] 2) 10 g of sodium carboxymethyl cellulose and 15 g of pentaerythritol dimethacrylate were added to an alcohol-water mixed solvent, and the above mixture was added, the reaction temperature was controlled at 50° C., stirred, centrifuged, and dried to obtain the product.

[0040] The average particle size of the zirconium silicate microbeads is 2 μm.

[0041] The particle size of the nano aluminum silicate is 20-50 nm.

[0042] The particle size of the silicon dioxide is 20-50 nm.

[0043] The coupling agent is γ-(2,3 epoxypropyl)propyltrimethoxysilane.

[0044] The crosslinking agent is methyltriacetoxysilane and methyltributylidene oxime silane, and the mass ratio of the two is 1:1.

[0045] The catalyst is dibutyltin dilaurate.

[0046] The viscosity of the α,ω-dihydroxypolydimethylsiloxane is 30000 cps.

[0047] The viscosity of the vinyl silicone oil is 500 cps.

[0048] The viscosity of the hydrogen-containing silicone oil is 350 cps.

[0049] The preparation method of the high-performance sealant provided in this embodiment comprises the following steps:

[0050] 1) Disperse and stir α,ω-dihydroxy polydimethylsiloxane, vinyl silicone oil, hydrogen silicone oil and crosslinking agent for 25 minutes;

[0051] 2) Add flame retardant, fumed silica and silicon nitride and stir at high speed for 30 minutes;

[0052] 3) adding a coupling agent and a catalyst, evacuating the mixture, stirring for 80 minutes under a vacuum degree of -0.05 MPa, and then discharging the mixture to obtain the high-performance sealant.

[0053] Example 2

[0054] This embodiment provides a high-performance sealant, comprising the following components in parts by weight:

[0055] 100 parts of α,ω-dihydroxypolydimethylsiloxane, 10 parts of vinyl silicone oil, 5 parts of hydrogenated silicone oil, 10 parts of flame retardant, 6 parts of fumed silica, 4 parts of silicon nitride, 10 parts of coupling agent, 10 parts of crosslinking agent, and 0.2 parts of catalyst;

[0056] The preparation method of the flame retardant is:

[0057] 1) Add 5 g zirconium silicate microbeads, 2 g nano aluminum silicate, and 2 g nano silicon dioxide into 10 mL water and grind thoroughly to obtain a mixture;

[0058] 2) 10 g of sodium carboxymethyl cellulose and 15 g of pentaerythritol dimethacrylate were added to an alcohol-water mixed solvent, and the above mixture was added, the reaction temperature was controlled at 50° C., stirred, centrifuged, and dried to obtain the product.

[0059] The average particle size of the zirconium silicate microbeads is 5 μm.

[0060] The particle size of the nano aluminum silicate is 20-50 nm.

[0061] The particle size of the silicon dioxide is 20-50 nm.

[0062] The coupling agent is γ-(2,3 epoxypropyl)propyltrimethoxysilane.

[0063] The crosslinking agent is methyl tributylidene oxime silane.

[0064] The catalyst is dibutyltin diacetate.

[0065] The viscosity of the α,ω-dihydroxypolydimethylsiloxane is 20000 cps.

[0066] The viscosity of the vinyl silicone oil is 500 cps.

[0067] The viscosity of the hydrogen-containing silicone oil is 350 cps.

[0068] The preparation method of the high-performance sealant provided in this embodiment comprises the following steps:

[0069] 1) Disperse and stir α,ω-dihydroxy polydimethylsiloxane, vinyl silicone oil, hydrogen silicone oil and crosslinking agent for 25 minutes;

[0070] 2) Add flame retardant, fumed silica and silicon nitride and stir at high speed for 25 minutes;

[0071] 3) adding a coupling agent and a catalyst, evacuating the mixture, stirring for 80 minutes under a vacuum degree of -0.05 MPa, and then discharging the mixture to obtain the high-performance sealant.

[0072] Example 3

[0073] This embodiment provides a high-performance sealant, comprising the following components in parts by weight:

[0074] 100 parts of α,ω-dihydroxypolydimethylsiloxane, 25 parts of vinyl silicone oil, 10 parts of hydrogen silicone oil, 30 parts of flame retardant, 8 parts of fumed silica, 7 parts of silicon nitride, 15 parts of coupling agent, 18 parts of crosslinking agent, and 0.3 parts of catalyst;

[0075] The preparation method of the flame retardant is:

[0076] 1) Add 5 g zirconium silicate microbeads, 2 g nano aluminum silicate, and 2 g nano silicon dioxide into 10 mL water and grind thoroughly to obtain a mixture;

[0077] 2) 10 g of sodium carboxymethyl cellulose and 15 g of pentaerythritol dimethacrylate were added to an alcohol-water mixed solvent, and the above mixture was added, the reaction temperature was controlled at 50° C., stirred, centrifuged, and dried to obtain the product.

[0078] The average particle size of the zirconium silicate microbeads is 2 μm.

[0079] The particle size of the nano aluminum silicate is 20-50 nm.

[0080] The particle size of the silicon dioxide is 20-50 nm.

[0081] The coupling agent is γ-glycidyloxypropyltrimethoxysilane.

[0082] The crosslinking agent is methyltriacetoxysilane.

[0083] The catalyst is dibutyltin bis(acetylacetonate).

[0084] The viscosity of the α,ω-dihydroxypolydimethylsiloxane is 30000 cps.

[0085] The viscosity of the vinyl silicone oil is 500 cps.

[0086] The viscosity of the hydrogen-containing silicone oil is 350 cps.

[0087] The preparation method of the high-performance sealant provided in this embodiment comprises the following steps:

[0088] 1) Disperse and stir α,ω-dihydroxy polydimethylsiloxane, vinyl silicone oil, hydrogen silicone oil and crosslinking agent for 25 minutes;

[0089] 2) Add flame retardant, fumed silica and silicon nitride and stir at high speed for 30 minutes;

[0090] 3) adding a coupling agent and a catalyst, evacuating the mixture, stirring for 80 minutes under a vacuum degree of -0.05 MPa, and then discharging the mixture to obtain the high-performance sealant.

[0091] Comparative Example 1

[0092] Compared with Example 1, the difference is that no vinyl silicone oil and hydrogen-containing silicone oil are added, and the other components are the same.

[0093] The preparation method is the same as that of Example 1.

[0094] Comparative Example 2

[0095] Compared with Example 1, the difference is that no hydrogen-containing silicone oil is added, and the other components are the same.

[0096] The preparation method is the same as that of Example 1.

[0097] Comparative Example 3

[0098] Compared with Example 1, the difference is that no vinyl silicone oil is added, and the other components are the same.

[0099] The preparation method is the same as that of Example 1.

[0100] Comparative Example 4

[0101] Compared with Example 1, the difference is that no flame retardant is added, and other components are the same.

[0102] The preparation method is the same as that of Example 1.

[0103] Comparative Example 5

[0104] Compared with Example 1, the difference is that the aluminum silicate microbeads in the flame retardant are replaced with zirconium silicate, and the other components are the same.

[0105] The preparation method is the same as that of Example 1.

[0106] Comparative Example 6

[0107] Compared with Example 1, the difference is that the flame retardant is zirconium silicate, aluminum silicate and silicon dioxide, and the other components are the same.

[0108] The preparation method is the same as that of Example 1.

[0109] Comparative Example 7

[0110] Compared with Example 1, the difference is that no fumed silica and silicon nitride are added, and the other components are the same.

[0111] The preparation method is the same as that of Example 1.

[0112] Comparative Example 8

[0113] Compared with Example 1, the differences are: the added amount of flame retardant is 5, the added amount of fumed silica is 5 parts, the added amount of silicon nitride is 5 parts, and the other components are the same.

[0114] The preparation method is the same as that of Example 1.

[0115] Performance Test:

[0116] 1. Mechanical properties test: Test the tensile strength according to the method specified in GB / T 528-1998.

[0117] 2. Temperature resistance test: The cured test piece is aged at 180°C for 7 days, cooled to room temperature and its tensile strength is tested.

[0118] 3. Light aging test: at an average irradiance of 0.5W / m 2 The light aging test was carried out at a plate temperature of 60°C and an experimental time of 600 h. After aging, the samples were air-dried at room temperature for 24 h and their tensile strength was tested.

[0119] 4. Flame retardant performance test: According to GB / T 10707-2008 standard, the limiting oxygen index test is carried out on the sample with the size of 100mm×6mm×2mm.

[0120] The test results are shown in Table 1.

[0121] Table 1 Performance test results

[0122]

[0123] It can be seen from Table 1 that the high-performance sealants provided by Examples 1-3 of the present invention have better tensile strength, high temperature resistance, light aging resistance and flame retardancy.

[0124] Compared with Example 1, in Comparative Examples 1-3, where no two or one of vinyl silicone oil and hydrogen-containing silicone oil were added, the tensile strength decreased, and the decrease was greater when both vinyl silicone oil and hydrogen-containing silicone oil were not added at the same time, indicating that α, ω-dihydroxypolydimethylsiloxane can be better synergistically improved in combination with vinyl silicone oil and hydrogen-containing silicone oil to improve the mechanical properties of the sealant.

[0125] Compared with Example 1, in Comparative Example 4, no flame retardant was added, and the tensile strength, high temperature resistance, light aging resistance and flame retardancy were significantly reduced, wherein the oxygen index was lower than 28%, indicating that the flame retardant provided by the present invention can significantly improve the flame retardancy, and at the same time, improve the mechanical properties within the ratio range of the present invention, and improve the high temperature resistance and light aging resistance.

[0126] Compared with Example 1, in Comparative Example 5, the aluminum silicate microbeads in the flame retardant are replaced with zirconium silicate, and the tensile strength, high temperature resistance, light aging resistance and flame retardancy decrease to a certain extent, indicating that the aluminum silicate microbeads of the present invention have a better effect of improving the mechanical and flame retardant properties of the sealant.

[0127] Compared with Example 1, the flame retardant of Comparative Example 6 is a mixture of zirconium silicate, aluminum silicate and silicon dioxide. The tensile strength, high temperature resistance, light aging resistance and flame retardancy are significantly reduced. The reason may be that the inorganic powder particles have poor dispersibility. In this addition amount range, the tensile strength is greatly reduced, and its high temperature resistance, light aging resistance and flame retardancy are affected.

[0128] Compared with Example 1, in Comparative Example 7, no fumed silica and silicon nitride were added, and the tensile strength, high temperature resistance, light aging resistance and flame retardancy decreased to a certain extent, indicating that silica and silicon nitride can coordinate with flame retardants to improve the mechanical properties and flame retardancy of the sealant.

[0129] Compared with Example 1, the addition ratio of the flame retardant, white carbon black and silicon nitride in Comparative Example 8 is not within the suitable compatibility range of the present invention, and the tensile strength, high temperature resistance, light aging resistance and flame retardancy are all reduced, especially the flame retardancy is poor, and its oxygen index is 25.4%, which is significantly lower than 28%.

[0130] It can be seen from the test results of the above embodiments and comparative examples that the sealant of the present invention has good mechanical properties, and still maintains good mechanical properties after high-temperature aging and light aging, maintains a good bonding effect, can avoid the adhesive layer from falling off when used in extreme environments, optimizes the sealing quality, and has a high oxygen index of up to 37.5%, and has excellent flame retardant properties.

[0131] Although the embodiments of the present description have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present description, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A high performance sealant, characterized in that: The invention comprises the following components in parts by weight: 100 parts of α, ω-dihydroxy polydimethylsiloxane, 10-25 parts of vinyl silicone oil, 5-10 parts of hydrogen silicone oil, 10-40 parts of flame retardant, 5-10 parts of fumed silica, 3-8 parts of silicon nitride, 10-15 parts of coupling agent, 10-20 parts of crosslinking agent and 0.1-1 parts of catalyst; the preparation method of the flame retardant is as follows: 1) adding water to zirconium silicate microbeads, nano aluminum silicate and nano silicon dioxide to fully grind to obtain a mixture; 2) adding sodium carboxymethyl cellulose and pentaerythritol dimethacrylate to the mixture; into a solvent, stirred, added with the above mixture, the reaction temperature controlled to 40-50° C., and dried to obtain the product; the mass ratio of the zirconium silicate microbeads, nano aluminum silicate, nano silicon dioxide, sodium carboxymethyl cellulose, and pentaerythritol dimethacrylate is 3-5:1-2:1-2:5-10:10-20; the mass ratio of the flame retardant: fumed silica: silicon nitride is 3-5:1-2:0.3-2; the catalyst is one or more of dibutyltin bis(acetylacetonate), dibutyltin diacetate, and dibutyltin dilaurate.

2. A high performance sealant according to claim 1, characterized in that: The particle size of the zirconium silicate microbeads is 1-10 μm.

3. A high performance sealant according to claim 1, characterized in that: The particle size of the nano aluminum silicate is 1-100 nm.

4. A high performance sealant according to claim 3, characterized in that: The particle size of the nano aluminum silicate is 20-50 nm.

5. A high performance sealant according to claim 1, characterized in that: The particle size of the nano silicon dioxide is 1-100 nm.

6. A high performance sealant according to claim 5, characterized in that: The particle size of the nano silicon dioxide is 20-50 nm.

7. A high performance sealant according to claim 1, characterized in that: The coupling agent is one or more of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and γ-(2,3 epoxypropyl)propyltrimethoxysilane.

8. A high performance sealant according to claim 1, characterized in that: The crosslinking agent is one or more of methyl triacetoxysilane, ethyl triacetoxysilane, propyl triacetoxysilane, methyl tributylidene oxime silane and di-tert-butoxy diacetoxy silane.

9. The method for preparing the high-performance sealant according to any one of claims 1 to 8, characterized in that: The following steps are involved: 1) Disperse and stir α, ω-dihydroxy polydimethylsiloxane, vinyl silicone oil, hydrogen-containing silicone oil and crosslinking agent for 20-30 minutes; 2) Add flame retardant, fumed silica and silicon nitride and stir at high speed for 25-40 minutes; 3) Add coupling agent and catalyst, evacuate, disperse and stir evenly and then discharge.

10. Use of the high performance sealant according to any one of claims 1 to 8, characterized in that: The applications include bonding of door and window materials, bonding of prefabricated building components, bonding of fireproof facility materials, and bonding of automotive materials.

Citation Information

Patent Citations

  • A method for preparing an environmentally friendly silicone sealant

    CN109762514B

  • A flame-retardant modified silane sealant and its preparation method

    CN116694288B

  • Mono-component room-temperature vulcanized silicone heat-insulation refractory sealant and preparation method thereof

    CN102516925A

  • Reactive flame-retardant porcelainized powder and reinforced flame-retardant porcelainized organic silicon elastomer using same

    CN113087969A